PERISI: a computer program for preliminary evaluation of rainfall-induced slope instability - Gofar, Nurly (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2009)
This paper introduces a computer program PERISI stands for Preliminary Evaluation of Rainfall-Induced Slope Instability. The program was developed by utilizing the concept of extreme rainfall and unique relationships between rainfall characteristics, hydraulic conductivity, suction, and water content of unsaturated soil to evaluate the minimum suction distribution in soil. The outcome of the program is the factor of safety of soil slope in the critical condition as compared to normal condition.